Investigation of bacterial antigenic fragments OMPs as a potential vaccine candidate against vibriosis in TGGG - Iffah Md Daud; Rukmiyatul Rahim; Cahyo Budiman; Mohd Tamrin Lal; Zarina Amin (Penerbit UMS, 2024)
Aquaculture holds a crucial position in the economies of developing nations, making significant contribution to both food security and income. Despite its importance, aquaculture encounters challenges including bacterial infections threats like vibriosis that caused by Vibrio spp. Concerns regarding antibiotic resistance have prompted a shift towards usage of vaccine as a sustainable alternative treatment method. This study focused on the development of a fusion fragment protein GADPH-OmpK as a potential vaccine candidate against vibriosis in hybrid TGGG Grouper (Epinephelus fuscoguttatus x E. lanceolatus) and the impact it has on the expression of immune genes. The fusion fragment protein was successfully overexpressed and used to intraperitoneally immunize hybrid TGGG grouper. The immunogenetic expression of Interleukin-2, Interleukin-6 and Interferon-ϒ in the results indicated that the vaccine elicits a considerable immune response in the fish, demonstrating its potential in enhancing aquaculture sustainability. Overall, this research presents a promising avenue for advancing aquaculture practices and mitigating antibiotic resistance issues in fish farming since recombinant protein vaccine offer various advantages.